FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MUDHARABAH PADA BANK UMUM SYARIAH DI INDONESIA - Jamilah, Jamilah; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of Third Party Fund (DPK), Capital Adequacy Ratio(CAR), and Return on Asset (ROA), Non Performing Financing (NPF), and The Operating Cost to theOperating Revenue (BOPO) and mudharabah financing. The population of this research is bank umum syariahwhich are listed in Bank Indonesia during the 2011-2014 periods by using quarter financial statement. Theresearch sample has been selected by using purposive sampling so that 10 bank umum syariah (160 firm threemonths) which meet the criteria have been selected as samples. The analysis technique has been done by usingmultiple regressions have been done by using SPSS program 22.0 version. Based on the result of multipleregressions, it shows that Third Party Funds (DPK) has positive influence to the mudharabah financing; capitaladequacy ratio has positive influence to the mudharabah financing, return on asset has negative influence to themudharabah financing, non performing financing does not have any positive influence to the mudharabahfinancing, operating cost to the operating revenue (BOPO) has negative influence to the mudharabah financing.Keywords: Third Party Fund, Capital Adequacy Ratio, Return on Asset, Non Performing Financing, TheOperating Cost to the Operating Revenue, and mudharabah financing.